English major education in China: a chronological analysis - Li, Min; Hu, Xuhui (Onomázein, 2021)
This paper offers an overview over the development of China’s English major in higher educational institutions since 1977 in different stages: the restoration period (1977-1986), developing period (1987-1997), prosperity period (1998-2009), and adjustment period (2010-present). The problems and controversy over this major are also introduced and analysed. Overall, this paper aims to inform readers of the recent history and current situation of the English major in Chinese universities, which might also shed light on the studies of the language related programs in universities in general.